Indoor exposures and respiratory symptoms in a Norwegian community sample. Issue 11 (29th July 2005) - Duelien Skorge, T; Eagan, T M L; Eide, G E; Gulsvik, A; Bakke, P S
Abstract : Background: Limited data are available on the effect of a poor indoor climate on the respiratory health of adults. No data are available regarding the contribution of indoor exposures to the burden of respiratory symptoms in the population. Methods: In 1996–7 a community sample of 3181 adults aged 26–82 years was invited to participate in a survey on indoor climate and respiratory health in Hordaland County, Norway. 2401 subjects agreed to take part. Logistic regression was used to examine the relationship between eight markers of indoor exposure and physician diagnosed asthma and five respiratory symptoms, after adjustment for sex, age, smoking, educational level, smoking habits, pack years, and occupational airborne exposure. Results: Mould exposure was associated with all the respiratory symptoms; the adjusted odds ratios (OR) varied from 1.6 (95% confidence interval (CI) 1.0 to 2.4) for cough with phlegm to 2.3 (95% CI 1.4 to 3.9) for grade 2 dyspnoea. Keeping a cat or dog in childhood was associated with grade 2 dyspnoea and attacks of dyspnoea, with adjusted ORs of 1.3 (95% CI 1.0 to 1.7) and 1.4 (95% CI 1.1 to 1.8), respectively. Having a fitted carpet in the bedroom was negatively associated with three of the five respiratory symptoms. 3–5% of the frequency of the respiratory symptoms in the study population could be attributed to exposure to visible moulds. Conclusion: Mould exposure is an independent risk factor for several respiratory symptoms in a general population covering a wide age span, but it makes only a small contribution to the respiratory symptom burden in the population at large.